THE DEVELOPMENT OF THE «LEXICON OF HUMILITY» IN CHURCH SLAVONIC AND OLD UKRAINIAN BIBLICAL MONUMENTS OF THE 16TH CENTURY - LEVKO, Oleksandr (Linguistic and Conceptual Worldviews, 2022)
The article traces the origins of the formation of Ukrainian «lexicon of humility» in Old Ukrainian biblical monuments of the 16th century. It explores the use of Church Slavonic смиренїє / смгренїє «humility» and смирен(н)ьш / смгрень «humble» vis-a-vis покора «meekness» and покорньи «meek» of the «prosta mova» for the denotion of humility in the Peresopnytsia Gospel (1556-1561) and the Krekhiv Apostle (second half of the 16th century) as compared to the vocabulary use in the Ostroh Bible (1581), the Lviv Apostle (1574) and modern Ukrainian Bible translations.Bible translations of the early modern Ukraine, written in the Old Ukrainian «prosta mova», demonstrate two concurrent tendencies in the rendition of the «lexicon of humility»: following the Church Slavonic tradition (the Peresopnytsia Gospel) and employing Old Ukrainian words of «prosta mova» (the Krekhiv Apostle). While modern Bible translations tend to take into consideration the contextual meanings of the Greek words for humility and to render them with various lexical means of the Ukrainian language, this is not typical of the Church Slavonic biblical monuments of the 16th century, but is partially traceable in the Krekhiv Apostle.Obviously, the use of derivatives from смиренний and покірний in modern Ukrainian language is rooted in the religious monuments of the 16th and 17th centuries, written in «prosta mova», which signifies their considerable influence upon the formation of modern Ukrainian ethical lexicon.Modern Bible translations mostly render the positive meaning of ransivorppoiTwn / Taneivmmq and тапємод with the words покора / покірливість «meekness» and покірний / покірливий «meek», replacing the words of Church Slavonic origin смирення «humility» and смиренний «humble». The same tendency can be observed in the Krekhiv Apostle and the 17th century Didactic Gospels, which consistently use покора and покорньи. Modern Bible translations usually render the negatively connotated words for humility (conveying humiliation, oppression, destitution, etc.) with the derivatives from принижувати «humiliate», понижувати «lower», зневажати «despise», впокорювати «submit», quite similarly to the Krekhiv Apostle and Didactic Gospels, which employ the verbs унижити «humiliate», понижати «lower»and упокорити / упокоритися «submit / be submitted» in this function.
Keywords: Bible, «prosta mova», Church Slavonic, humility, Peresopnytsia Gospel, Krekhiv Apostle, Bible translation